2017
DOI: 10.1037/sgd0000204
|View full text |Cite
|
Sign up to set email alerts
|

Sexual minority status and interpersonal victimization in college men.

Abstract: Sexual minority men are at increased risk for sexual victimization at all ages compared to heterosexual men; yet, most research on victimization focuses on the experiences of heterosexual women. This study compares the rates of multiple forms of interpersonal violence (violence perpetrated by another person) in a sample of sexual minority status college men and heterosexual men on campus. Participants (n = 53 sexual minority men, n = 364 heterosexual) completed an anonymous web survey containing measures of ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…In their studies, Crowe (2020) andFindley et al (2015) noted that individuals with disabilities had increased levels of psychological distress and difficulties which were associated with discrimination, poor mental health, impaired self-efficacy and lower self-esteem, as well as intimate partner violence as a result of compulsive diffusion of intimate/sexually explicit images. The findings in this study provided support for previous studies among deaf individuals who reported a relationship between self-efficacy and reported incidents of negative behaviour and stressful life events, such as sexting (Lenhart, 2009;Makgale and Platterner, 2017), sexual and physical assault (Anderson et al, 2017;Crowe, 2020;Mahat and Scoloveno, 2010), alcohol abuse (Christiansen et al, 2002) and communication and social barriers (Cuevas et al, 2019;Marschark et al, 2018). This study found self-concept to be a negatively significant factor that influenced intimate image diffusion among deaf adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…In their studies, Crowe (2020) andFindley et al (2015) noted that individuals with disabilities had increased levels of psychological distress and difficulties which were associated with discrimination, poor mental health, impaired self-efficacy and lower self-esteem, as well as intimate partner violence as a result of compulsive diffusion of intimate/sexually explicit images. The findings in this study provided support for previous studies among deaf individuals who reported a relationship between self-efficacy and reported incidents of negative behaviour and stressful life events, such as sexting (Lenhart, 2009;Makgale and Platterner, 2017), sexual and physical assault (Anderson et al, 2017;Crowe, 2020;Mahat and Scoloveno, 2010), alcohol abuse (Christiansen et al, 2002) and communication and social barriers (Cuevas et al, 2019;Marschark et al, 2018). This study found self-concept to be a negatively significant factor that influenced intimate image diffusion among deaf adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…Considering sexual orientation, cisgender sexual minority college men reported nearly 5 times higher rates of rape acknowledgment than their heterosexual peers (22.7% vs. 4.3%; Anderson, Wandrey, Klossner, Cahill, & Delahanty, 2017). In addition to sexual orientation differences in rape acknowledgment, there are gender differences in rape acknowledgment.…”
Section: Sexual Violence and Sgmsmentioning
confidence: 98%
“…Survivors of IPV often have been exposed to CAN, and studies have directed attention towards this association by examining lifetime victimization in interpersonal relationships-childhood maltreatment and IPV-in LGB individuals (Anderson, Wandrey, Klossner, Cahill, & Delahanty, 2017;Balsam et al, 2005). The trajectory between CAN and IPV is supported by the social learning theory (Bandura, 1977), which postulates that children learn how to behave in intimate partnerships through modeling relationships they are exposed to during their childhood.…”
Section: Associations Between Can and Ipvmentioning
confidence: 99%